The contributions of the christian church to poverty creation in Nigeria (2019)
Poverty is a global phenomenon and various Solutions have been proffered by scholars over the years to reduce it. Attempts by government, Non-Governmental Organizations (NGOs), government agencies and individuals to alleviate the menace have continued to generate avalanche of debate from both national and international agencies and, most importantly, in Nigeria. Existing studies on poverty have focused mainly on how churches in Nigeria have made efforts to alleviate poverty through the setting up of various poverty alleviation programmes to better the lots of the people. Yet, an area which seems to have been largely ignored which requires a serious academic engagement is how churches have endangered the economic Standard of its members through various teachings and programmes that do not have any direct impact on the economic life of the people, thereby making them to continue to wallow in abject poverty. The methodologies employed are oral interview and materials that are relevant to the subject matter. Therefore, this work will, among other things, examine how churches in Nigeria have endangered the economic lives of their members. Lastly, recommendations will be offered on how the church leaders will re-direct their teachings to focus more on how to improve the living Standard of their members.